Dual-path multilayer substrate integrated waveguide circular cavity filter / Siti Aminah Nordin ... [et al.] - Nordin, Siti Aminah; Khan, Zuhani Ismail; Ab Wahab, Norfishah; Othman, N.; K. A, Nur Dalila; Wahid, S. S. A. (Universiti Teknologi MARA, 2019)
A dual-path multilayer substrate integrated waveguide circular cavity filter is introduces in this paper. The proposed dual-path multilayer circular cavity are designed between range 4.79 GHz to 4.85 GHz is thus suitable for wireless communication applications including DCS, WiMax, WLAN, WiBro, Bluetooth and C-band applications such as satellite communications, and weather radar systems. Two circular cavity based on SIW are connected via connect hole and probe which is attached at both side of the microstrip feed lines. Width and length of the feed lines probes have the ability to control the filter performances in terms of insertion and return loss. Measured response from fabricated filter shows resonant frequencies at 4.79 GHz and 5.05 GHz, and measured insertion loss found higher than simulation result around 4.47 dB. Consideration during fabrication and assembly process are required to avoid higher losses. The performances of the filter in terms of return loss, insertion loss and resonant frequency are analyzed in both simulations and measurement to validate the concept.